2011
DOI: 10.1007/s10535-011-0028-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium on gas exchange and phytohormone contents in citrus

Abstract: The effect of increased Cd 2+ concentrations in the watering solution on citrus physiology was studied by using two citrus genotypes, Cleopatra mandarin and Carrizo citrange. Cadmium content in roots and leaves was tested together with measurements of leaf damage, gas exchange parameters, and hormonal contents. Citrus roots efficiently retained Cd 2+ avoiding its translocation to the shoots and Cleopatra mandarin translocated less Cd 2+ than Carrizo. With increasing Cd 2+ concentration all gas exchange paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…To this regard, the selection of markers for phenotype assessment is not trivial. For instance, when considering tolerance to salt stress, the ability to maintain growth under high salinity even with high Na + leaf concentrations, was considered a tolerance trait in barley [113]. This is in contrast with salt stress mechanisms in other glycophytes, for instance, in citrus where the ability to reduce Cl − uptake to the aerial part is considered a tolerance trait [114].…”
Section: Effect Of Abiotic Stress On Plant Biochemistry: Metabolitmentioning
confidence: 99%
“…To this regard, the selection of markers for phenotype assessment is not trivial. For instance, when considering tolerance to salt stress, the ability to maintain growth under high salinity even with high Na + leaf concentrations, was considered a tolerance trait in barley [113]. This is in contrast with salt stress mechanisms in other glycophytes, for instance, in citrus where the ability to reduce Cl − uptake to the aerial part is considered a tolerance trait [114].…”
Section: Effect Of Abiotic Stress On Plant Biochemistry: Metabolitmentioning
confidence: 99%
“…Among pollutants, heavy metals such as cadmium (Cd), copper (Cu), lead and mercury are of particular concern as they are non-biodegradable and strongly phytotoxic. Furthermore, at high concentration, they not only limit plant productivity but also threaten human health (López-Climent et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of Cd-induced stomatal closure is still poorly understood. Some studies reported increased production of abscisic acid (ABA) with increased Cd-exposure and suggested that ABA might regulate stomata closure in Cd-stressed conditions (Hsu & Kao, 2003Lòpez-Climent et al, 2011); however, in ABA-insensitive mutants of Arabidopsis thaliana (L.) Heynh Cd 2+ affected guard cell regulation in an ABA-independent manner by entering the cytosol via Ca 2+ channels (Perfus-Barbeoch et al, 2002).…”
Section: Introductionmentioning
confidence: 99%